2007
DOI: 10.1021/ef070132e
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry of C−C and C−H Bond Breaking in Fatty Acid Methyl Esters

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…This species is beyond the calculating capacities of our Gaussian‐hardware combination, which does not exceed 8–12 heavy atoms. We had to relay solely on the value estimated using Catoire's single point DFT method 21.…”
Section: Calculationsmentioning
confidence: 99%
“…This species is beyond the calculating capacities of our Gaussian‐hardware combination, which does not exceed 8–12 heavy atoms. We had to relay solely on the value estimated using Catoire's single point DFT method 21.…”
Section: Calculationsmentioning
confidence: 99%
“…31 The results for these compounds were also compared to those for alcohol and alkane combustion 32 obtained in a previous study. It was found that oxygen-bearing functional groups within various 33 C8-C16 fuel molecules have a significant influence on the ignition delay and on engine in-cylinder 34 temperatures. Carbonyl compounds had longer ignition delays compared to the corresponding alkanes, 35 whereas ether compounds decreased the ignition delay.…”
mentioning
confidence: 99%
“…However, the carbonyl group 387 strengthens the C-H bonds of the next three carbon atoms in the 388 carbon chain making H-abstraction of the six hydrogen atoms 389 (labelled p in Methyl octanoate -Fig. 1) bonded to these carbon 390 atoms more difficult than abstraction of hydrogen atoms bonded 391to secondary carbon atoms of an alkane (labelled s in alkane -[33,34]. It is suggested that this strengthening of the Cabstraction, Fisher et al[35] suggested that the methyl-ester398 peroxy radical may go through a similar isomerization route to 399 alkane isomerization.…”
mentioning
confidence: 99%
“…Because of the lack of experimental information, the calculated results (in our case only the enthalpy of formation) are compared in the present paper with a new DFT method adopted by Catoire et al 21–25 and also with the former group additivity estimates to assess the strong and the weak points of the group additivity method.…”
Section: Calculationsmentioning
confidence: 99%
“…Since the compounds investigated in the present work are all chlorinated and brominated species of strained architecture and have no experimental data available, it was necessary to compare the G3B3 enthalpy of formation values with some other means of calculations. In view of our hardware limitations, we decided to use a DFT method recently adopted by Catoire et al 21–25 mainly for big molecules that cannot be calculated with the G3 family of methods. This is a simpler method than G3B3 to estimate enthalpies of formation.…”
Section: Calculationsmentioning
confidence: 99%